The influence of training characteristics and tapering on the adaptation in highly trained individuals: a review - Mujika, I. (International Journal of Sports Medicine, 1998)
In the general population, the adaptation to training seems to be dependent on factors such as training intensity, volume and frequency, and the initial level of fitness. In highly trained athletes, however, training intensity and initial performance level appear to be the most important factors influencing the response to training, and therefore competition performance, provided that necessary training volume and frequency are assured. When preparing for a major competition, athletes tend to reduce their training load for a variable period of time. This technique, known as taper, can have a major influence on the athlete's performance. The response to taper may be affected by the degree to which training intensity, volume and frequency are reduced, as well as by the combined effects of these variables. A thorough review of the available literature suggests that training volume and frequency can be reduced to a higher extent than training intensity, if falling into detraining is to be avoided. Moreover, the duration of the taper period and the time constant of decay of the training load can also affect the response to taper. Indeed, slow progressive reductions appear to be more effective than sudden standardized reductions in improving the athlete's performance level.